HYDROPERICARDIUM HEPATITIS SYNDROME AND VACCINATION WITH INFECTED LIVER EXTRACT - Khamas, Emad J.; Hana, Laith M. (The Iraqi Journal of Veterinary Medicine, 2000)
The experiment was carried out to evaluate a killed vaccine of HHS prepared from liver extract treated with (0.1%) formalin . The vaccine was injected Sc. Or. im. At (12) or (12,20) days old broilers . At age of 25 days, chicks were challenged with HHS liver extract . The vaccinated chicks showed full protection with no clinical signs or pathological changes .